When the African novel revisits History - (:unkn) unknown (My University, 2016)
The study focuses on the relationship between literature and history, specifically on the recovery of literature in history. Indeed, under certain fictions shows that the historical fact comes to feed the contents of the texts. In other words, the historical fact is a reservoir in which writers will draw material from their works. However if there is agreement on the principle that the literary text draws from history, it is clear that the historical material can be exploited for various purposes. So one wonders about the motives of the authors that tap into the past.We bring this issue to two African writers: Mongo Beti and Patrice Nganang. We will discuss the expected effects by these authors that use history. The exploration of the past, enabling them to position itself, is a pretext, a way for them to forge a new consciousness. In their works, the historical dimension is used to formulate socio-political approaches to criticize the established order, to affirm the role and place of the writer in the literary field. It is their status as a writer who is redefined
Keywords: African Research